Does the Legislature Want to Keep ‘The Marital Power of Husband’ In Black Letters? - Towards Save The Harmonious Co-Existence of The Law of Thesawalamai With Other Laws of Sri Lanka - Purathani, M. (8th International Symposium-2018 South Eastern University of Sri Lanka, 2018)
Generally, the customary laws treat women inequitably as far as their property rights within the marriage are concerned. Although a married woman, under the common law of the Island, the Kandyan and Muslim law, can handle her properties as a femme sole but not under the Thesawalamai due to the application of the concept of marital power. The discrimination is a reflection of the patriarchal system where the man is the head of the family and can have the control over the others. Thus the impact of the marital power causes injustice to the women who are governed by the Thesawalamai in the post-conflict Sri Lanka. Although the voices raised for the repeal of the concept of marital power under the Thesawalamai, the legislature intentionally kept the principle on the footing that the concept of marital power was derived from the customary practice of the community and the Constitution of 1978 expressly recognized such customary law despite the inconsistency with the fundamental rights provisions. Therefore, this research intends to study the origin and development of the marital power and its incorporation into the Theswalamai to ascertain whether the marital power was exercised as of a customary practice of the people governed by the Thesawalamai. The result of this study proposes the means to balance the customary values with the modern human rights standards. It is a qualitative mode of study based on the ordinances, judicial decisions, and academic writings.
Keywords: Marital Power; The law of Thesawalamai; Patriarchal Family; Married Women; Property rights